Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Hằng

loading...Giúp mình câu này nhé

 

Nguyễn Lê Phước Thịnh
17 tháng 8 2024 lúc 11:21

\(1+tan^2\alpha=\dfrac{1}{cos^2\alpha}\)

=>\(\dfrac{1}{cos^2\alpha}=1+\left(\dfrac{5}{12}\right)^2=1+\dfrac{25}{144}=\dfrac{169}{144}\)

=>\(cos^2\alpha=\dfrac{144}{169}\)

mà \(cos\alpha< 0\left(\Omega< \alpha< \dfrac{3}{2}\Omega\right)\)

nên \(cos\alpha=-\dfrac{12}{13}\)

\(tan\alpha=\dfrac{sin\alpha}{cos\alpha}\)

=>\(sin\alpha=-\dfrac{12}{13}\cdot\dfrac{5}{12}=-\dfrac{5}{13}\)

\(\Omega< \alpha< \dfrac{3}{2}\Omega\)

=>\(\dfrac{\Omega}{2}< \dfrac{\alpha}{2}< \dfrac{3}{4}\Omega\)

=>\(cos\left(\dfrac{\alpha}{2}\right)< 0;sin\left(\dfrac{\alpha}{2}\right)>0\)

\(cos\alpha=cos\left(2\cdot\dfrac{\alpha}{2}\right)=2\cdot cos^2\left(\dfrac{\alpha}{2}\right)-1\)

=>\(2\cdot cos^2\left(\dfrac{\alpha}{2}\right)-1=-\dfrac{12}{13}\)

=>\(2\cdot cos^2\left(\dfrac{\alpha}{2}\right)=1-\dfrac{12}{13}=\dfrac{1}{13}\)

=>\(cos^2\left(\dfrac{\alpha}{2}\right)=\dfrac{1}{26}\)

mà \(cos\left(\dfrac{\alpha}{2}\right)< 0\)

nên \(cos\left(\dfrac{\alpha}{2}\right)=-\dfrac{1}{\sqrt{26}}\)

\(sin^2\left(\dfrac{\alpha}{2}\right)+cos^2\left(\dfrac{\alpha}{2}\right)=1\)

=>\(sin^2\left(\dfrac{\alpha}{2}\right)=1-\left(\dfrac{1}{26}\right)=\dfrac{25}{26}\)

mà \(sin\left(\dfrac{\alpha}{2}\right)>0\)

nên \(sin\left(\dfrac{\alpha}{2}\right)=\dfrac{5}{\sqrt{26}}\)

\(cos\left(\dfrac{3}{2}\alpha\right)=cos\left(\alpha+\dfrac{1}{2}\alpha\right)\)

\(=cos\alpha\cdot cos\left(\dfrac{1}{2}\alpha\right)-sin\alpha\cdot sin\left(\dfrac{1}{2}\alpha\right)\)

\(=-\dfrac{12}{13}\cdot\dfrac{-1}{\sqrt{26}}-\dfrac{5}{\sqrt{26}}\cdot\dfrac{-5}{13}=\dfrac{12}{13\sqrt{26}}+\dfrac{25}{13\sqrt{26}}=\dfrac{37}{13\sqrt{26}}\)


Các câu hỏi tương tự
Nguyễn My
Xem chi tiết
Nguyễn Hồ Yến Nhi
Xem chi tiết
Givemesome Flan
Xem chi tiết
Givemesome Flan
Xem chi tiết
Givemesome Flan
Xem chi tiết
Kiến Văn
Xem chi tiết
Givemesome Flan
Xem chi tiết
Givemesome Flan
Xem chi tiết
Trâm Bảo
Xem chi tiết
Minh Nguyệt
Xem chi tiết